Exploring the Protective Effects of Surfactants against Corrosion: A Comprehensive Review - Adhikari, Manoj Kumar; Yadav, Chandradip Kumar; Chaudhary, Suni; Yadav, Amar Prasad; Bhattarai, Ajaya (Journal of Institute of Science and Technology, 2024)
Corrosion is the spontaneous chemical or electrochemical reaction of metal with its surrounding environment. There have been ongoing worries about how corrosion affects the strength and stability of metal surfaces. Chemical corrosion inhibitors are often used in manufacturing and processing activities to prevent the deterioration of materials. Surfactants are a highly affordable, readily available, and environmentally friendly choice for corrosion inhibitors. This article outlines surfactants' capacity to prevent corrosion on various metal surfaces. The properties of multiple surfactants and their possible applications for corrosion inhibitors have also been discussed. This review article also explores additional factors, such as how varying levels of surfactants contribute to the mechanisms behind corrosion inhibition.